2000
DOI: 10.1029/1999jd900773
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur chemistry in the National Center for Atmospheric Research Community Climate Model: Description, evaluation, features, and sensitivity to aqueous chemistry

Abstract: Abstract.Sulfur chmnistry has been incorporated in the National Center [or Atmospheric Research Community Climate Model in an internally consistent manner with other parameterizations in the model. The model predicts mixing ratios of dimethylsulfide (DMS), SO2, SO•-, H202. Processes that control the mixing ratio of these species include the emissions of DMS and SO2, transport of each species, gas-and aqueous-phase chemistry, wet deposition, and dry deposition of species. Modeled concentrations agree quite well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
356
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(383 citation statements)
references
References 73 publications
(9 reference statements)
22
356
5
Order By: Relevance
“…This simplistic approach has been used in global models (Barth et al, 2000). We find that the global and annual mean aerosol mass burdens in simulation F100 are lower in comparison to the CTL simulation, by up to 10% for sulfate.…”
Section: Impacts On Predicted Aerosol Massmentioning
confidence: 91%
See 2 more Smart Citations
“…This simplistic approach has been used in global models (Barth et al, 2000). We find that the global and annual mean aerosol mass burdens in simulation F100 are lower in comparison to the CTL simulation, by up to 10% for sulfate.…”
Section: Impacts On Predicted Aerosol Massmentioning
confidence: 91%
“…100% of the aerosols in clouds are assumed to be scavenged into the droplets or crystals for the simulation F100. This simplistic assumption has been used in global models (e.g., Barth et al, 2000). The simulation F100-INT is similar except that 100% of the soluble/internally mixed aerosols in clouds are assumed to be cloud-borne, and 0% of the insoluble aerosol is scavenged into the cloud droplets or crystals.…”
Section: In-cloud Scavenging Sensitivity Simulationsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has generally been found that SO 4 or NH 4 show fairly constant concentrations over wide areas (Pakkanen et al, 2001). Following Adams et al (1999), the source of particulate ammonium is from the condensation of gaseous ammonia, whilst those of particulate SO 4 are from condensation of gaseous sulfuric acid, and SO 2 to sulfate conversion (Barth et al, 2000). The major source (>73%) of SO 2 in Hong Kong is from power generation in the western part of the Territory ( CH2M Hill, 2002).…”
Section: Mean Concentrations Of Inorganic Components In Pm 10 and Intmentioning
confidence: 99%
“…Mari et al, 2000;Barth et al, 2000). The equilibrium between the gas phase and the liquid phase is given by the effective Henry's constant (Sander, 1999) and is not reached for all species on each model time step.…”
Section: Introductionmentioning
confidence: 99%